Safety and immunogenicity of a candidate Middle East respiratory syndrome coronavirus viral-vectored vaccine: a dose-escalation, open-label, non-randomised, uncontrolled, phase 1 trial. Issue 7 (July 2020) - Folegatti, Pedro M; Bittaye, Mustapha; Flaxman, Amy; Lopez, Fernando Ramos; Bellamy, Duncan; Kupke, Alexandra; Mair, Catherine; Makinson, Rebecca; Sheridan, Jonathan; Rohde, Cornelius; Halwe, Sandro; Jeong, Yuji; et al.
Summary: Background: Cases of Middle East respiratory syndrome coronavirus (MERS-CoV) infection continue to rise in the Arabian Peninsula 7 years after it was first described in Saudi Arabia. MERS-CoV poses a significant risk to public health security because of an absence of currently available effective countermeasures. We aimed to assess the safety and immunogenicity of the candidate simian adenovirus-vectored vaccine expressing the full-length spike surface glycoprotein, ChAdOx1 MERS, in humans. Methods: This dose-escalation, open-label, non-randomised, uncontrolled, phase 1 trial was done at the Centre for Clinical Vaccinology and Tropical Medicine (Oxford, UK) and included healthy people aged 18–50 years with negative pre-vaccination tests for HIV antibodies, hepatitis B surface antigen, and hepatitis C antibodies (and a negative urinary pregnancy test for women). Participants received a single intramuscular injection of ChAdOx1 MERS at three different doses: the low-dose group received 5 × 10 9 viral particles, the intermediate-dose group received 2·5 × 10 10 viral particles, and the high-dose group received 5 × 10 10 viral particles. The primary objective was to assess safety and tolerability of ChAdOx1 MERS, measured by the occurrence of solicited, unsolicited, and serious adverse events after vaccination. The secondary objective was to assess the cellular and humoral immunogenicity of ChAdOx1 MERS, measured by interferon-γ-linked enzyme-linked immunospot, ELISA, and virus neutralising assays after vaccination. Participants were followed up for up to 12 months. This study is registered with ClinicalTrials.gov, NCT03399578 . Findings: Between March 14 and Aug 15, 2018, 24 participants were enrolled: six were assigned to the low-dose group, nine to the intermediate-dose group, and nine to the high-dose group. All participants were available for follow-up at 6 months, but five (one in the low-dose group, one in the intermediate-dose group, and three in the high-dose group) were lost to follow-up at 12 months. A single dose of ChAdOx1 MERS was safe at doses up to 5 × 10 10 viral particles with no vaccine-related serious adverse events reported by 12 months. One serious adverse event reported was deemed to be not related to ChAdOx1 MERS. 92 (74% [95% CI 66–81]) of 124 solicited adverse events were mild, 31 (25% [18–33]) were moderate, and all were self-limiting. Unsolicited adverse events in the 28 days following vaccination considered to be possibly, probably, or definitely related to ChAdOx1 MERS were predominantly mild in nature and resolved within the follow-up period of 12 months. The proportion of moderate and severe adverse events was significantly higher in the high-dose group than in the intermediate-dose group (relative risk 5·83 [95% CI 2·11–17·42], p<0·0001) Laboratory adverse events considered to be at least possibly related to the study intervention were self-limiting and predominantly mild in severity. A significant increase from baseline in T-cell (p<0·003) and IgG (p<0·0001) responses to the MERS-CoV spike antigen was observed at all doses. Neutralising antibodies against live MERS-CoV were observed in four (44% [95% CI 19–73]) of nine participants in the high-dose group 28 days after vaccination, and 19 (79% [58–93]) of 24 participants had antibodies capable of neutralisation in a pseudotyped virus neutralisation assay. Interpretation: ChAdOx1 MERS was safe and well tolerated at all tested doses. A single dose was able to elicit both humoral and cellular responses against MERS-CoV. The results of this first-in-human clinical trial support clinical development progression into field phase 1b and 2 trials. Funding: UK Department of Health and Social Care, using UK Aid funding, managed by the UK National Institute for Health Research.